Features of Modern Higher Education in the USA: STEM Education - Batyuk, Liliya; Masych, Vitalii (Educological discourse, 2025)
Obtaining higher education in the United States of America is a key catalyst for social mobility of the population, public confidence, which provides many individual advantages in modern society. In 2023-2024, graduates of higher education institutions in the United States will make up a larger share of employees in both public and private enterprises, compared to those with a lower level of education. The economic and social development of Ukraine, as a world leader, requires investment in education. In this regard, it is relevant to study the implementation of STEM education in higher education institutions in the United States of America, since over the past three decades the importance of STEM education for the country's economic competitiveness has been recognized by the United States Government as a level of official resolutions, laws and regulations, as an area that supports the development of ideas and solutions necessary to solve the country's global problems. The article examines the impact of the decentralization of the US higher education sector on the strategy, oversight, and accreditation of higher education institutions in the United States. The presence of independent and autonomous accreditation agencies in the US that can assess the performance of US higher education institutions is analyzed. The procedure for assessing the performance of US higher education institutions, which is implemented through funding for needs-based research, innovative programs, and individual federal loans, is analyzed, and covers such university areas as student education, management, academic programs, faculty and staff qualifications, and finance. The specifics of the distribution of STEM degrees in the field of bachelor’s and master’s degrees in private and public institutions are considered. The concept of «conceptualizing culture» in undergraduate STEM education is investigated. The influence of curators and teachers of STEM disciplines on the ability of students to succeed in STEM education is investigated. It has been determined that STEM education in the United States is characterized by support from the Federal Government and is the national educational framework of the United States, which ensures the competitiveness of the state in the field of future employment.